Establishing the Delphi Technique for Validity Measure of Employability Skills in Industrial Work Practice Program - Yutima, Ellydza; Suseno, Muchlas; Dudung, Agus (LPPM Undiksha, 2022)
Research instruments in program evaluation are essential and need thorough care regarding validity, reliability, and credibility. This study aims to verify the skills required in the Industrial Job Training Program applicable to Astra Honda repair shops. The Delphi analysis technique was used in this study to reach a consensus among experts on the skills required for motorcycle engineers. The participants of this research were six panelists using the purposive technique. Data were collected through document analysis, questionnaires, and follow-up interviews. The instrument used to collect data is a questionnaire sheet. The consensus among six experts in rating skills is then calculated using SPSS 24 software to perform W analysis. The research results are, first, experts prioritize mastery of soft skills over technical skills. It can be proven by the ranking results, which place soft skills in the top 7 rankings ahead of all technical skill items. Second, among the many technical skills presented from the government's proposed curriculum and Honda's traditional skills, experts selected only the most specific and specialized skills that were most widely applied in the workplace. It was concluded that experts prefer workers who excel in soft skills compared to technical skills.